Transition metal-based composite material for photocatalytic organic reaction and preparation method of transition metal-based composite material

By acidizing the multi-walled carbon nanotubes and crosslinking them with porphyrin acid chloride, a network structure with high crosslinking degree is formed, and then reacting with transition metal salts, the problems of poor light absorption effect and low catalytic activity of existing composite materials are solved, and an efficient photocatalytic organic reaction is achieved.

CN119702080AActive Publication Date: 2025-03-28CHONGQING UNIV OF EDUCATION +1

Patent Information

Application Number
CN202411904716.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing composite materials based on transition metal functional groups have poor light absorption effect and low catalytic activity in photocatalytic organic reactions, which affects the photocatalytic efficiency and stability, and limits their wide application.

Method used

By acidizing the multi-walled carbon nanotubes, hydroxyl and carboxy active groups are introduced, and cross-linking reaction with porphyrin acid chloride, a network structure with high cross-linking degree is formed, and finally reacted with the transition metal salt to form a metalporphyrin composite material.

Benefits of technology

It significantly improves the photocatalytic activity and efficiency of composite materials, enhances its absorption range and intensity of light, improves the stability of photocatalytic organic reactions, and makes it have great promotion value in industrial and scientific research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204117520000121
    Figure BDA0005204117520000121
  • Figure BDA0005204117520000131
    Figure BDA0005204117520000131
Patent Text Reader

Abstract

The invention relates to the field of photocatalytic organic reactions, in particular to a transition metal-based composite material for photocatalytic organic reactions and a preparation method of the transition metal-based composite material, and aims to solve the problems that an existing composite material based on transition metal functional groups is poor in light absorption effect and low in catalytic activity, and photocatalytic efficiency and photocatalytic stability are affected. And the wide application is limited. According to the preparation method, metalloporphyrin molecules with a high crosslinking degree are grafted on the surfaces of the carbon nanotubes, the number of active sites participating in a photocatalytic reaction is effectively increased, so that the photocatalytic activity is remarkably enhanced, and metalloporphyrin and the carbon nanotubes can exert unique advantages respectively and are matched with each other, so that the photocatalytic activity is improved. Through the synergistic effect of the two, photon energy can be more effectively absorbed, and generation and separation of photon-generated carriers are accelerated, so that the photocatalytic activity of the composite material is greatly improved, the efficiency and stability of a photocatalytic organic reaction can be remarkably improved, and the whole composite material is extremely excellent in the photocatalytic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photocatalytic organic reactions, and in particular to a transition metal-based composite material for photocatalytic organic reactions and a preparation method thereof. Background Art

[0002] Photocatalytic organic reactions, as an efficient, green and controllable synthesis method, have attracted much attention in recent years. With the continuous development of science and technology, photocatalytic organic reactions have important application prospects in the fields of organic synthesis and environmental protection. Among them, composite materials based on transition metal functional groups have become the frontier research direction of efficient photocatalysts due to their good photocatalytic performance, low preparation cost and easy-to-regulate active sites. Common composite materials of this type include transition metal oxides, metal organic frameworks, etc., but their photocatalytic efficiency is still limited by the performance of the system itself and the absorption characteristics limited to the visible light region, resulting in poor light absorption effect and low catalytic activity, affecting the photocatalytic efficiency and photocatalytic stability, and limiting their wide application.

[0003] Therefore, developing a transition metal-based composite material for photocatalytic organic reactions and a preparation method thereof has important theoretical significance and practical application value. Summary of the invention

[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a transition metal-based composite material for photocatalytic organic reactions and a preparation method thereof, which solves the problems that the existing composite materials based on transition metal functional groups have poor light absorption effect and low catalytic activity, which affect the photocatalytic efficiency and photocatalytic stability and limit their wide application.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] The preparation method of a transition metal-based composite material for photocatalytic organic reaction comprises the following steps:

[0007] Step 1: Add multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 1-1.5 hours at an ultrasonic frequency of 40-50kHz, and then stir and react for 1-1.5 hours at a temperature of 25-30°C and a stirring rate of 300-400r / min, and then continue to stir and react for 5-6 hours at a temperature of 80-85°C. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is washed with distilled water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 2-3 hours to obtain acidified carbon nanotubes;

[0008] Step 2: Add the acidified carbon nanotubes and thionyl chloride into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then heat the temperature to 80-85°C and stir the reaction for 10-15h. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water for 3-5 times, then place it in a vacuum drying oven, and dry it at a temperature of 60-65°C for 2-3h to obtain acyl chloride carbon nanotubes;

[0009] Step 3: adding meso-tetrakis (4-carboxyphenyl) porphine, N, N-dimethylformamide and chloroform to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introducing nitrogen protection, stirring the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 1-1.5 h, then adding thionyl chloride and heating to reflux and continuing to stir the reaction for 5-6 h, after the reaction is completed, cooling the reaction product to room temperature, and then rotary evaporation to remove the solvent to obtain porphyrin chloride;

[0010] Step 4: Add chlorinated carbon nanotubes, chlorinated porphyrin, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide and anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 2-2.5 hours at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then add triethylenetetramine and continue stirring and reacting for 20-30 hours. After the reaction is completed, centrifuge the reaction product, wash the precipitate with distilled water 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 30-35° C. for 3-4 hours to obtain cross-linked porphyrin grafted carbon nanotubes;

[0011] Step 5: Add cross-linked porphyrin grafted carbon nanotubes, N, N-dimethylformamide and chloroform to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 20-25 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add a transition metal salt and continue stirring and reacting for 20-30 hours at a temperature of 130-135°C. After the reaction, the reaction product is cooled to room temperature, and then washed with anhydrous ethanol and distilled water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 80-85°C for 8-10 hours to obtain a transition metal-based composite material for photocatalytic organic reactions.

[0012] As a further solution of the present invention: the usage ratio of the multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step 1 is 2g:60-65mL:20-25mL.

[0013] As a further solution of the present invention: the average tube diameter of the multi-walled carbon nanotubes in step 1 is 80 nm, and the average tube length is 20 μm.

[0014] As a further solution of the present invention: the mass fraction of the concentrated sulfuric acid is 96-98%.

[0015] As a further solution of the present invention: the mass fraction of the concentrated nitric acid is 65-68%.

[0016] As a further solution of the present invention: the usage ratio of the acidified carbon nanotubes and thionyl chloride in step 2 is 0.1 g: 20-25 mL.

[0017] As a further solution of the present invention: the usage ratio of the meso-tetrakis(4-carboxyphenyl)porphine, N,N-dimethylformamide, chloroform and thionyl chloride in step 3 is 1 g: 7-9 mL: 50-55 mL: 1.5-3.5 mL.

[0018] As a further scheme of the present invention: the usage ratio of the chlorinated carbon nanotubes, chlorinated porphyrin, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, anhydrous methanol and triethylenetetramine in step 4 is 0.1g: 0.5-1.1g: 0.3-0.5g: 0.3-0.5g: 80-100mL: 0.5-0.9g.

[0019] As a further solution of the present invention: the usage ratio of the cross-linked porphyrin grafted carbon nanotubes, N,N-dimethylformamide, chloroform and transition metal salt in step five is 1g:7-9mL:50-55mL:9-13g.

[0020] As a further solution of the present invention: the transition metal salt in step five is one of zinc acetate dihydrate, cobalt acetate tetrahydrate and manganese acetate tetrahydrate.

[0021] As a further solution of the present invention: the transition metal-based composite material for photocatalytic organic reaction is prepared according to the preparation method of the transition metal-based composite material for photocatalytic organic reaction according to the claim.

[0022] Beneficial effects of the present invention:

[0023] The transition metal-based composite material for photocatalytic organic reaction and the preparation method thereof are as follows: multi-walled carbon nanotubes are treated with a mixed acid of concentrated sulfuric acid and concentrated nitric acid to remove impurities thereon, and active groups such as hydroxyl groups and carboxyl groups are introduced thereon to obtain acidified carbon nanotubes; then the acidified carbon nanotubes are treated with thionyl chloride to convert the carboxyl groups thereon into acyl chloride groups to enhance the reaction activity thereof, thereby obtaining acyl chloride carbon nanotubes; then meso-tetrakis(4-carboxyphenyl)porphine is treated with thionyl chloride to convert the carboxyl groups thereon into acyl chloride groups to enhance the reaction activity thereof, thereby obtaining acyl chloride porphyrin; then triethylenetetramine is used to treat the acidified carbon nanotubes; The acyl chloride carbon nanotube and acyl chloride porphyrin are treated so that the three are fully cross-linked to form a network structure with a high degree of cross-linking, thereby obtaining cross-linked porphyrin grafted carbon nanotubes. Finally, the cross-linked porphyrin grafted carbon nanotubes and transition metal salts are reacted, and the porphyrin rings on the cross-linked porphyrin grafted carbon nanotubes and the transition metal ions in the transition metal salts form a complex to form metal porphyrin, thereby obtaining a transition metal-based composite material for photocatalytic organic reactions. Porphyrin has a large conjugated structure and has a strong absorption capacity for visible light. After the transition metal ions are coordinated therein, the light absorption characteristics of the metal porphyrin can be affected, thereby changing the electron distribution of the porphyrin ring, thereby improving its The absorption range and intensity of light are rich in metal porphyrins with excellent light absorption ability. When exposed to light, the electrons in the metal porphyrin molecules are excited from the ground state to the excited state, providing an energy basis for the subsequent photocatalytic reaction. Carbon nanotubes are good conductive materials, and under the irradiation of light, the electrons in the carbon nanotubes are excited to form photogenerated electrons and holes. These photogenerated electrons and holes are highly active and can participate in subsequent redox reactions. Therefore, metal porphyrins and carbon nanotubes are fully cross-linked to form a network structure, so that the metal porphyrins and carbon nanotubes have a close interaction, making the two like building a bridge. An efficient bridge, metalloporphyrin and carbon nanotubes each play a unique advantage and cooperate with each other. When light is irradiated on the transition metal-based composite material, in the process of electron transfer, the synergistic effect of the two can more effectively absorb photon energy and accelerate the generation and separation of photogenerated carriers, thereby greatly improving the photocatalytic activity of the composite material, and can significantly improve the efficiency and stability of photocatalytic organic reactions, so that the entire composite material performs extremely well in photocatalytic reactions; moreover, the preparation method is simple, efficient, and reproducible, which is conducive to industrial production, making it have great promotion value in actual industrial production and scientific research. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Embodiment 1:

[0026] This embodiment is a method for preparing a transition metal-based composite material for photocatalytic organic reaction, comprising the following steps:

[0027] Step 1: Add 2g of multi-walled carbon nanotubes with an average tube diameter of 80nm and an average tube length of 20μm, 60mL of concentrated sulfuric acid with a mass fraction of 96% and 20mL of concentrated nitric acid with a mass fraction of 65% into a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 1h at an ultrasonic frequency of 40kHz, then stir and react for 1h at a temperature of 25°C and a stirring rate of 300r / min, then continue to stir and react for 5h under the condition of heating to 80°C, and after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 3 times, and then place it in a vacuum drying oven and dry it at a temperature of 60°C for 2h to obtain acidified carbon nanotubes;

[0028] Step 2: Add 0.1 g of acidified carbon nanotubes and 20 mL of thionyl chloride to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 20 min at a temperature of 25 ° C and a stirring rate of 300 r / min, then heat to 80 ° C and stir and react for 10 h. After the reaction, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 3 times, and then place it in a vacuum drying oven and dry it at a temperature of 60 ° C for 2 h to obtain acyl chloride carbon nanotubes;

[0029] Step 3: Add 1 g of meso-tetrakis(4-carboxyphenyl)porphine, 7 mL of N,N-dimethylformamide and 50 mL of chloroform to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 1 h at a temperature of 25 ° C and a stirring rate of 300 r / min, then add 1.5 mL of thionyl chloride and continue stirring and reacting for 5 h under the condition of heating to reflux, and after the reaction is completed, cool the reaction product to room temperature, and then remove the solvent by rotary evaporation to obtain porphyrin chloride;

[0030] Step 4: 0.1 g of chlorinated carbon nanotubes, 0.5 g of chlorinated porphyrin, 0.3 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, 0.3 g of N-hydroxysuccinimide and 80 mL of anhydrous methanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred for 2 h at a temperature of 25 ° C and a stirring rate of 300 r / min, and then 0.5 g of triethylenetetramine was added and the stirring reaction was continued for 20 h. After the reaction was completed, the reaction product was centrifuged, and the precipitate was washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 30 ° C for 3 h to obtain cross-linked porphyrin grafted carbon nanotubes;

[0031] Step 5: Add 1g of cross-linked porphyrin grafted carbon nanotubes, 7mL of N,N-dimethylformamide and 50mL of chloroform to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, and stir the reaction for 20min at a temperature of 25°C and a stirring rate of 300r / min. Then, add 9g of zinc acetate dihydrate and continue stirring the reaction for 20h under the condition of heating to 130°C. After the reaction, the reaction product is cooled to room temperature, and then washed with anhydrous ethanol and distilled water for 3 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 80°C for 8h to obtain a transition metal-based composite material for photocatalytic organic reactions.

[0032] Embodiment 2:

[0033] This embodiment is a method for preparing a transition metal-based composite material for photocatalytic organic reaction, comprising the following steps:

[0034] Step 1: Add 2g of multi-walled carbon nanotubes with an average tube diameter of 80nm and an average tube length of 20μm, 62mL of concentrated sulfuric acid with a mass fraction of 97% and 22mL of concentrated nitric acid with a mass fraction of 67% into a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 1.2h at an ultrasonic frequency of 45kHz, then stir and react for 1.2h at a temperature of 28°C and a stirring rate of 350r / min, then continue to stir and react for 5.5h under the condition of heating to 82°C, and after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 4 times, and then place it in a vacuum drying oven and dry it at a temperature of 62°C for 2.5h to obtain acidified carbon nanotubes;

[0035] Step 2: Add 0.1 g of acidified carbon nanotubes and 22 mL of thionyl chloride to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 25 min at a temperature of 28 ° C and a stirring rate of 350 r / min, then heat to 82 ° C and stir and react for 12 h. After the reaction, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 4 times, and then place it in a vacuum drying oven and dry it at a temperature of 62 ° C for 2.5 h to obtain acyl chloride carbon nanotubes;

[0036] Step 3: 1 g of meso-tetrakis (4-carboxyphenyl) porphine, 8 mL of N, N-dimethylformamide and 52 mL of chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for 1.2 h at a temperature of 28 ° C and a stirring rate of 350 r / min, and then 2.5 mL of thionyl chloride was added and the temperature was raised to reflux and the stirring reaction was continued for 5.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain porphyrin chloride;

[0037] Step 4: 0.1 g of chlorinated carbon nanotubes, 0.8 g of chlorinated porphyrin, 0.4 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, 0.4 g of N-hydroxysuccinimide and 90 mL of anhydrous methanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The reaction was stirred for 2.2 h at a temperature of 28 ° C and a stirring rate of 350 r / min, and then 0.7 g of triethylenetetramine was added and the stirring reaction was continued for 25 h. After the reaction was completed, the reaction product was centrifuged, and the precipitate was washed 4 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 32 ° C for 3.5 h to obtain cross-linked porphyrin grafted carbon nanotubes;

[0038] Step 5: Add 1g of cross-linked porphyrin grafted carbon nanotubes, 8mL of N,N-dimethylformamide and 52mL of chloroform to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 22min at a temperature of 28°C and a stirring rate of 350r / min, then add 11g of cobalt acetate tetrahydrate and continue stirring and reacting for 25h under the condition of heating to 132°C. After the reaction, the reaction product is cooled to room temperature, and then washed with anhydrous ethanol and distilled water for 4 times in turn, and then placed in a vacuum drying oven and dried at a temperature of 82°C for 9h to obtain a transition metal-based composite material for photocatalytic organic reactions.

[0039] Embodiment 3:

[0040] This embodiment is a method for preparing a transition metal-based composite material for photocatalytic organic reaction, comprising the following steps:

[0041] Step 1: Add 2g of multi-walled carbon nanotubes with an average tube diameter of 80nm and an average tube length of 20μm, 65mL of concentrated sulfuric acid with a mass fraction of 98% and 25mL of concentrated nitric acid with a mass fraction of 68% into a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 1.5h at an ultrasonic frequency of 50kHz, then stir and react for 1.5h at a temperature of 30°C and a stirring rate of 400r / min, then continue to stir and react for 6h under the condition of heating to 85°C, and after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 5 times, and then place it in a vacuum drying oven and dry it at a temperature of 65°C for 3h to obtain acidified carbon nanotubes;

[0042] Step 2: Add 0.1 g of acidified carbon nanotubes and 25 mL of thionyl chloride to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir the reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, then heat the temperature to 85° C. and stir the reaction for 15 h. After the reaction is completed, cool the reaction product to room temperature, then centrifuge it, wash the precipitate with distilled water 5 times, then place it in a vacuum drying oven, and dry it at a temperature of 65° C. for 3 h to obtain acyl chloride carbon nanotubes;

[0043] Step 3: Add 1 g of meso-tetrakis(4-carboxyphenyl)porphine, 9 mL of N,N-dimethylformamide and 55 mL of chloroform to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 1.5 h at a temperature of 30 ° C and a stirring rate of 400 r / min, then add 3.5 mL of thionyl chloride and continue stirring and reacting for 6 h under the condition of heating to reflux, and after the reaction is completed, cool the reaction product to room temperature, and then remove the solvent by rotary evaporation to obtain porphyrin chloride;

[0044] Step 4: 0.1 g of chlorinated carbon nanotubes, 1.1 g of chlorinated porphyrin, 0.5 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.5 g of N-hydroxysuccinimide and 100 mL of anhydrous methanol were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 2.5 h, and then 0.9 g of triethylenetetramine was added and the stirring reaction was continued for 30 h. After the reaction was completed, the reaction product was centrifuged, and the precipitate was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 35° C. for 4 h to obtain cross-linked porphyrin grafted carbon nanotubes;

[0045] Step 5: Add 1g of cross-linked porphyrin grafted carbon nanotubes, 9mL of N,N-dimethylformamide and 55mL of chloroform to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, and stir the reaction for 25min at a temperature of 30°C and a stirring rate of 400r / min. Then, add 13g of manganese acetate tetrahydrate and continue stirring the reaction for 30h under the condition of heating to 135°C. After the reaction, the reaction product is cooled to room temperature, and then washed with anhydrous ethanol and distilled water for 5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 10h to obtain a transition metal-based composite material for photocatalytic organic reactions.

[0046] Comparative Example 1:

[0047] This comparative example is a method for preparing a transition metal-based composite material for photocatalytic organic reaction, comprising the following steps:

[0048] 1 g of meso-tetrakis(4-carboxyphenyl)porphine, 9 mL of N,N-dimethylformamide and 55 mL of chloroform were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30°C and a stirring rate of 400 r / min for 25 minutes. Then, 13 g of manganese acetate tetrahydrate was added and the temperature was raised to 135°C and the stirring reaction was continued for 30 hours. After the reaction, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The product was then washed with anhydrous ethanol and distilled water for 5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 10 hours to obtain a transition metal-based composite material for photocatalytic organic reactions.

[0049] Comparative Example 2:

[0050] This comparative example is a method for preparing a transition metal-based composite material for photocatalytic organic reaction, comprising the following steps:

[0051] Step 1: 1 g of meso-tetrakis(4-carboxyphenyl)porphine, 9 mL of N,N-dimethylformamide and 55 mL of chloroform were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for 1.5 h at a temperature of 30° C. and a stirring rate of 400 r / min, and then 3.5 mL of thionyl chloride was added and the temperature was raised to reflux and the stirring reaction was continued for 6 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain chlorinated porphyrin;

[0052] Step 2: 1.1 g of chlorinated porphyrin, 0.5 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.5 g of N-hydroxysuccinimide and 100 mL of anhydrous methanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred for 2.5 h at a temperature of 30 ° C and a stirring rate of 400 r / min, and then 0.9 g of triethylenetetramine was added and the stirring reaction was continued for 30 h. After the reaction was completed, the reaction product was rotary evaporated to remove the solvent, and then washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 35 ° C for 4 h to obtain polyporphyrin;

[0053] Step 3: Add 1g of polyporphyrin, 9mL of N,N-dimethylformamide and 55mL of chloroform to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 25min at a temperature of 30°C and a stirring rate of 400r / min, then add 13g of manganese acetate tetrahydrate and continue stirring and reacting for 30h at a temperature of 135°C. After the reaction, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, then wash with anhydrous ethanol and distilled water 5 times in turn, then place in a vacuum drying oven, and dry at a temperature of 85°C for 10h to obtain a transition metal-based composite material for photocatalytic organic reactions.

[0054] Comparative Example 3:

[0055] This comparative example is a method for preparing a transition metal-based composite material for photocatalytic organic reaction, comprising the following steps:

[0056] Step 1: Add 2g of multi-walled carbon nanotubes with an average tube diameter of 80nm and an average tube length of 20μm, 65mL of concentrated sulfuric acid with a mass fraction of 98% and 25mL of concentrated nitric acid with a mass fraction of 68% into a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically disperse for 1.5h at an ultrasonic frequency of 50kHz, then stir and react for 1.5h at a temperature of 30°C and a stirring rate of 400r / min, then continue to stir and react for 6h under the condition of heating to 85°C, and after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 5 times, and then place it in a vacuum drying oven and dry it at a temperature of 65°C for 3h to obtain acidified carbon nanotubes;

[0057] Step 2: Add 0.1 g of acidified carbon nanotubes and 25 mL of thionyl chloride to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir the reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, then heat the temperature to 85° C. and stir the reaction for 15 h. After the reaction is completed, cool the reaction product to room temperature, then centrifuge it, wash the precipitate with distilled water 5 times, then place it in a vacuum drying oven, and dry it at a temperature of 65° C. for 3 h to obtain acyl chloride carbon nanotubes;

[0058] Step 3: Add 1 g of meso-tetrakis(4-carboxyphenyl)porphine, 9 mL of N,N-dimethylformamide and 55 mL of chloroform to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 1.5 h at a temperature of 30 ° C and a stirring rate of 400 r / min, then add 3.5 mL of thionyl chloride and continue stirring and reacting for 6 h under the condition of heating to reflux, and after the reaction is completed, cool the reaction product to room temperature, and then remove the solvent by rotary evaporation to obtain porphyrin chloride;

[0059] Step 4: Add 0.1g of chlorinated carbon nanotubes, 1.1g of chlorinated porphyrin, 9mL of N,N-dimethylformamide and 55mL of chloroform to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 25min at a temperature of 30°C and a stirring rate of 400r / min, then add 13g of manganese acetate tetrahydrate and continue stirring and reacting for 30h at a temperature of 135°C. After the reaction, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, then wash with anhydrous ethanol and distilled water 5 times in turn, then place in a vacuum drying oven, and dry at a temperature of 85°C for 10h to obtain a transition metal-based composite material for photocatalytic organic reactions.

[0060] The transition metal-based composite material for photocatalytic organic reaction is subjected to photocatalytic organic reaction test, and the test method is as follows:

[0061] 1. Catalytic Toluene Oxidation Reaction

[0062] Accurately weigh 0.1 g of the transition metal-based composite material for photocatalytic organic reaction from Examples 1-3 and Comparative Examples 1-3 and place it in a photochemical reactor, then weigh 2 g of toluene in the photochemical reactor, fix the reactor, turn on the constant temperature circulating condensation water system, control the condensation water temperature to 20 ° C, first use CO at a flow rate of 10 mL / min 2,The gas was purged into the photochemical reactor for 20 minutes to remove the air in the photochemical reactor, and then the gas outlet of the reactor was closed. The CO2 gas flow rate was changed to 5 mL / min and the photochemical reactor was continuously charged for 10 minutes to fill the reactor with CO2 gas. Then the CO2 gas cylinder was closed and the 300W xenon lamp was turned on. After the reaction for 11 hours, the xenon lamp and the circulating condensed water were turned off. The reacted solution was ultrasonicated twice, and all the products on the surface of the transition metal-based composite material for photocatalytic organic reaction were washed into ethyl acetate solution, and then vacuum filtered, and the filter cake was washed with ethyl acetate five times, and then the total amount of ethyl acetate was added to 98 g, and the toluene concentration in the sample was tested by GC9710-gas chromatograph, and the following formula was used:

[0063]

[0064] Where:

[0065] α 甲苯 is the toluene conversion rate;

[0066] C 初始甲苯 is the initial toluene concentration;

[0067] C 反应后甲苯 is the toluene concentration after the reaction;

[0068] 2. Catalytic reaction of CO2 and methanol to synthesize dimethyl carbonate

[0069] Accurately weigh 0.1 g of the transition metal-based composite material for photocatalytic organic reaction from Examples 1-3 and Comparative Examples 1-3 and place it in a photochemical reactor, then weigh 2 g of methanol in the photochemical reactor, fix the reactor, turn on the constant temperature circulating condensed water system, control the condensed water temperature to 20 ° C, first use a CO2 gas with a flow rate of 10 mL / min to purge the photochemical reactor for 20 min to remove the air in the photochemical reactor, then close the gas outlet of the reactor, change the CO2 gas flow rate to 5 mL / min and continue to blow into the photochemical reactor. The reactor was inflated for 10 minutes to fill the reactor with CO2 gas, then the CO2 cylinder was closed and the 300W xenon lamp was turned on. After 11 hours of reaction, the xenon lamp and the circulating condensed water were turned off, and the solution after the reaction was ultrasonicated twice to wash all the products on the surface of the transition metal-based composite material for photocatalytic organic reaction into ethyl acetate solution, and then vacuum filtered, and the filter cake was washed with ethyl acetate five times, and then the total amount of ethyl acetate was added to 98g, and the methanol concentration in the sample was tested by GC9710-gas chromatograph, and the following formula was used:

[0070]

[0071] Where:

[0072] α甲醇 is the methanol conversion rate;

[0073] C 初始甲醇 is the initial methanol concentration;

[0074] C 反应后甲醇 is the methanol concentration after the reaction.

[0075] The test results are shown in the following table:

[0076] sample Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[α 甲苯 ,%]]> 88.14 90.39 95.53 78.45 86.92 90.06 <![CDATA[α 甲醇 ,%]]> 58.74 60.76 66.58 44.25 49.87 55.16

[0077] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be known that the transition metal-based composite material for photocatalytic organic reaction in the present invention has excellent photocatalytic performance and effectively catalyzes the progress of organic reactions.

[0078] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0079] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a transition metal-based composite material for photocatalytic organic reaction, characterized in that: The following steps are involved: Step 1: ultrasonically disperse multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid, and then stir to react. After the reaction is completed, the reaction product is cooled, centrifuged, and the precipitate is washed with distilled water and then dried to obtain acidified carbon nanotubes; Step 2: stirring the acidified carbon nanotubes and thionyl chloride to react, cooling the reaction product after the reaction is completed, then centrifuging, washing the precipitate with distilled water, and then drying to obtain acyl chloride carbon nanotubes; Step 3: stirring meso-tetrakis(4-carboxyphenyl)porphine, N,N-dimethylformamide and chloroform to react, then adding thionyl chloride and continuing stirring to react, cooling the reaction product after the reaction is completed, and then rotary evaporating to obtain porphyrin chloride; Step 4: stirring the chlorinated carbon nanotubes, chlorinated porphyrin, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and anhydrous methanol to react, then adding triethylenetetramine and continuing the stirring reaction, centrifuging the reaction product after the reaction is completed, washing the precipitate with distilled water, and then drying to obtain cross-linked porphyrin grafted carbon nanotubes; Step 5: Stir the cross-linked porphyrin grafted carbon nanotubes, N,N-dimethylformamide and chloroform to react, then add the transition metal salt and continue stirring the reaction. After the reaction is completed, cool the reaction product, then wash it with anhydrous ethanol and distilled water in turn, and then dry it to obtain a transition metal-based composite material for photocatalytic organic reactions.

2. The method for preparing a transition metal-based composite material for photocatalytic organic reaction according to claim 1, characterized in that: The usage ratio of the multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step 1 is 2g:60-65mL:20-25mL.

3. The method for preparing a transition metal-based composite material for photocatalytic organic reaction according to claim 1, characterized in that: The average tube diameter of the multi-walled carbon nanotubes in step 1 is 80 nm, the average tube length is 20 μm, the mass fraction of the concentrated sulfuric acid is 96-98%, and the mass fraction of the concentrated nitric acid is 65-68%.

4. The method for preparing a transition metal-based composite material for photocatalytic organic reaction according to claim 1, characterized in that: The usage ratio of the acidified carbon nanotubes and thionyl chloride in step 2 is 0.1 g: 20-25 mL.

5. The method for preparing a transition metal-based composite material for photocatalytic organic reaction according to claim 1, characterized in that: The dosage ratio of the meso-tetrakis(4-carboxyphenyl)porphine, N,N-dimethylformamide, chloroform and thionyl chloride in step 3 is 1 g: 7-9 mL: 50-55 mL: 1.5-3.5 mL.

6. The method for preparing a transition metal-based composite material for photocatalytic organic reaction according to claim 1, characterized in that: The amount ratio of the chlorinated carbon nanotubes, chlorinated porphyrin, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, anhydrous methanol and triethylenetetramine in step 4 is 0.1g: 0.5-1.1g: 0.3-0.5g: 0.3-0.5g: 80-100mL: 0.5-0.9g.

7. The method for preparing a transition metal-based composite material for photocatalytic organic reaction according to claim 1, characterized in that: In step 5, the amount ratio of the cross-linked porphyrin grafted carbon nanotubes, N,N-dimethylformamide, chloroform and transition metal salt is 1g:7-9mL:50-55mL:9-13g.

8. The method for preparing a transition metal-based composite material for photocatalytic organic reaction according to claim 1, characterized in that: The transition metal salt in step 5 is one of zinc acetate dihydrate, cobalt acetate tetrahydrate and manganese acetate tetrahydrate.

9. A transition metal-based composite material for photocatalytic organic reactions, characterized in that: The transition metal-based composite material for photocatalytic organic reaction is prepared according to the method for preparing the transition metal-based composite material for photocatalytic organic reaction according to any one of claims 1-8.

Citation Information

Patent Citations

  • Cobalt-embedded nitrogen-rich porous carbon material / self-assembled nano porphyrin composite photocatalyst as well as preparation method and application thereof

    CN113694963A

  • Preparation method and application of carbon nanotube loaded metalloporphyrin molecular catalyst

    CN117619443A

Cited By

  • A method of synthesizing benzocyclobutenedione

    CN122586697A